Evolution of Microstructure, Texture, and Mechanical Properties of As-Extruded ND/ZK60 Composite during Hot Compression Deformation - Jinhui Wang; Shangpeng Li; Hongbin Ma (Metals, 2020)
The effects of temperature, strain rate, and strain on the microstructure, texture, and mechanical properties of as-extruded nanodiamond reinforced ZK60 composite during hot compression was systematically studied. The results revealed that the precipitating MgZn2 and the nanodiamond (ND) particles distributed in the grain interiors hindered the motion of dislocations. The ND particles act as nucleation points and promote the dynamic recrystallization (DRX) of the composites during the hot compression deformation, the flow stress of ND/ZK60 increases with strain rate increases and temperature decreases. {10<semantics><mover accent="true">1¯</mover></semantics>2} extension twins are nucleated and grown in the coarse grains as the compressive strain increasing. Meanwhile, the fine grains of DRX generate and present first an increasing then a decreasing trend. The result of Schmid factor and kernel average misorientation indicates that high-density dislocation caused by dislocation climbing and cross slip aggregated in composites with increasing strain. Therefore, the work hardening trend of the composite is strengthened.